Quinazolin-4(3H)-one based potential multiple tyrosine kinase inhibitors with excellent cytotoxicity - Tebyan O. Mirgany; Ashraf N. Abdalla; Md Arifuzzaman; A. F. M. Motiur Rahman; Huda S. Al-Salem (Taylor & Francis Group, 2021)
A series of quinazolin-4(3H)-one derivatives were synthesised and evaluated for their cytotoxicity against human Caucasian breast adenocarcinoma (MCF-7) and human ovarian carcinoma (A2780) cell lines. Cytotoxicity of the most tested compounds was 2- to 30-fold more than the positive control lapatinib (IC50 of 2j = 3.79 ± 0.96; 3j = 0.20 ± 0.02; and lapatinib = 5.9 ± 0.74) against MCF7 cell lines except two compounds (IC50 of 2 b = 15.72 ± 0.07 and 2e = 14.88 ± 0.99). On the other hand, cytotoxicity was 4 − 87 folds (IC50 of 3a = 3.00 ± 1.20; 3 g = 0.14 ± 0.03) more the positive control lapatinib (IC50 = 12.11 ± 1.03) against A2780 cell lines except compound 2e (IC50 = 16.43 ± 1.80). Among the synthesised quinazolin-4(3H)-one derivatives, potent cytotoxic 2f-j and 3f-j were investigated for molecular mechanism of action. Inhibitory activities of the compounds were tested against multiple tyrosine protein kinases (CDK2, HER2, EGFR and VEGFR2) enzymes. As expected, all the quinazolin-4(3H)-one derivatives were showed comparable inhibitory activity against those kinases tested, especially, compound 2i and 3i showed potent inhibitory activity against CDK2, HER2, EGFR tyrosine kinases. Therefore, molecular docking analysis for quinazolin-4(3H)-one derivatives 2i and 3i were performed, and it was revealed that compounds 2i and 3i act as ATP non-competitive type-II inhibitor against CDK2 kinase enzymes and ATP competitive type-I inhibitor against EGFR kinase enzymes. However, in case of HER2, compounds 2i act as ATP non-competitive type-II inhibitor and 3i act as ATP competitive type-I inhibitor. Docking results of known inhibitors were compared with synthesised compounds and found synthesised 2i and 3i are superior than the known inhibitors in case of interactions. In addition, in silico drug likeness properties of quinazolin-4(3H)-one derivatives showed better predicted ADME values than lapatinib.